Biological differentiation of traditional Chinese medicine from excessive to deficient syndromes in AIDS: Comparative microRNA microarray profiling and syndrome‐specific biomarker identification. Issue 6 (17th December 2020) - Wan, Tingjun; Liu, Xiyang; Su, Yue; Zou, Jiaxi; Wu, Xi; Jiang, Cen; Cao, Chunhui; Yao, Mingyue; Zhou, Yuyu; Rong, Lijun; Li, Baixue; Wen, Li; et al.
Abstract: Traditional Chinese medicine (TCM) has been widely applied as a supplementary therapy of human immunodeficiency virus infection and acquired immunodeficiency syndrome (HIV/AIDS) in China. TCM has a positive effect on improving the quality of life, prolonging life, and ameliorating the symptoms of HIV/AIDS patients. Yang deficiency of spleen and kidney (YDSK) syndrome is a typical deficient TCM syndrome in AIDS patients, and accumulation of heat‐toxicity (AHT) syndrome is a common excessive syndrome in the earlier stage of AIDS. Thus, accurate diagnosis of these two syndromes can improve the targeted treatment effect, and predict the prognosis of the disease. However, the scientific basis of TCM syndromes remains lacking, greatly hindering the accuracy of diagnosis and effectiveness of treatment. In this research, microRNA (miRNA) microarray and quantitative real‐time polymerase chain reaction combined with bioinformatics were used for comparative analysis between YDSK and AHT patients. Significantly differential expressed miRNAs (SDE‐miRNAs) of each TCM syndrome were identified, including hsa‐miR‐766‐3p and hsa‐miR‐1260a and so on, as well hsa‐miR‐6124, hsa‐let‐7g‐5p and so on, for YDSK and AHT, respectively. Biological differences were found between their SDE‐miRNAs based on bioinformatics analyses, for example, ErbB signaling pathway mainly linked to AHT, while focal adhesion dominated in YDSK. Syndrome‐specific SDE‐miRNAs were further identified as potential biomarkers, including hsa‐miR‐30e‐5p, hsa‐miR‐144‐5p for YDSK and hsa‐let‐7g‐5p, hsa‐miR‐126‐3p for AHT, respectively. All of them have laid biological and clinical bases for TCM diagnosis and treatment of AIDS syndrome at the miRNA level, offering potential diagnostic indicators of immune reconstitution.